Deep-water fish assemblages in the Mediterranean Sea - d'Onghia, Gianfranco; Politou, Chrissi Yianna; Bozzano, Anna; Lloris, Domingo; Rotllant, Guiomar; Sión, Letizia; Mastrototaro, Francesco (Scientia Marina, 2004)
Data collected during the DESEAS survey carried out in three areas of the Mediterranean Sea (Balearic Sea, western and eastern Ionian Sea) were used to describe the structure and spatial distribution of the fish assemblages at depths between 600 and 4000 m. A total of 55 species (8 chondrichthyes and 47 teleost fish) were sampled, 38 of them in the Balearic Sea, 30 in the western Ionian and 37 in the eastern Ionian. Multivariate analysis showed a clear pattern of zonation with depth and geographic area. Three main assemblages were identified across the vertical gradient investigated: on the upper slope around a depth of 600 m, on the middle slope between 800 and 1300 m, and on the lower slope below 1300 m. The geographic characterisation of the ichthyofauna structure was mainly observed on the upper and middle slope. The highest abundance and biomass values were found at depths of 1000-1200 m due to the presence of larger species with high energy requirements, such as Alepocephalusrostratus, Mora moro and Galeus melastomus. On the middle slope, significant differences in the abundance, biomass and mean fish weight were detected between the three areas. Significant differences for these parameters were also shown between the middle and lower slope assemblages. A significant decrease in species richness and diversity was shown with increasing depth, indicating an impoverishment of the megafauna with depth and a higher similarity between the Balearic Sea and the Ionian Sea with regard to the greatest depths. The dominant species on the deepest bottoms were Bathypteroismediterraneus, Chalinura mediterranea and Coryphaenoides guentheri. On the lower slope, the shark Centroscymnuscoelolepis was also found to be relatively abundant off the Balearic Islands, Etmopterusspinax in the eastern Ionian Sea and the teleost fish Cataetyx laticeps throughout the three study areas. The deepest bottoms of the Mediterranean Sea shelter an ichthyofauna dominated by small-medium species living in a food scarce environment in which some large mobile fishes are widespread. The results are discussed in relation to previous studies mostly carried out in the Atlantic and western Mediterranean.